Development of E-Modules Based on Project Learning in Vocational High Schools - Muharikh Al Hanif; Budi Santosa (Universitas Ahmad Dahlan, 2023)
Research objectives is for developing e-modules based learning project that can support skills 21st century on the Basic Automotive Engineering lessons at School Intermediate Vocational / Vocational School. Research methods use ADDIE model with five stages, i. e Analyse, Design, Develop, Implement & Evaluate model (Branch, 2009). Analyze stage done for identify needs and challenges in learning the basics of automotive engineering as well as gather input from the stakeholders’ interests. Design and develop stage involve designing and creating e-modules based learning appropriate project with characteristics eye lessons and needs students. After e-module developed, stage implement product done for evaluate feasibility and effectiveness in support learning. Research and development results are: (1) basic learning of automotive engineering at Muhammadiyah Sungai Bahar Vocational High School is currently carried out using lecture, demonstration, and assignment methods; (2) the results of the development of basic automotive engineering learning at Vocational High Schools, namely by utilizing e-modules based on integrated project learning innovation skills; (3) the results of the homogeneity test of significance values in the control and experimental groups are based on an average value of 0.247 which is greater than (>) 0.05. Based on the Shapiro-Wilk normality test, the significance value is greater (>) than 0.05. The results of this research can improve the quality of learning in basic automotive engineering subjects using e-module technology based on integrated project learning innovation skills.